Purpose and Cause in Pauline Exegesis : Romans 1.16-4.25 and a New Approach to the Letters. - Dabourne, Wendy (Society for New Testament Studies Monograph Series, 104., 2003)
This book is about how to read Paul's letters as first-century epistles. A new method is worked out by studying Romans 1.16-4.25. The result is a presentation of Romans as a highly practical letter, in which we see justification by grace through faith as theology at work.